2005
DOI: 10.1038/labinvest.3700289
|View full text |Cite
|
Sign up to set email alerts
|

Activation of epithelial CD98 glycoprotein perpetuates colonic inflammation

Abstract: Anomalies in the regulation and function of integrins have been implicated in the etiology of various pathologic conditions, including inflammatory disorders such as irritable bowel disease. Several classes of cell surface glycoproteins such as CD98 have been shown to play roles in integrins-mediated events. Here, we investigated the role of CD98 in intestinal inflammation using both in vivo and in vitro approaches. We found that in Caco2-BBE monolayers and colonic tissues, expression of CD98 was upregulated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 28 publications
2
44
0
Order By: Relevance
“…overexpression promoted colonic tumorigenesis in mouse models of CAC by aggravating intestinal inflammation, with increased IEC proliferation and induction of proinflammatory cytokines and chemokines crucially contributing to tumor progression (2). Our previous studies demonstrated upregulation of CD98 expression in cultured IECs stimulated with proinflammatory cytokines (19,21), in colonic tissues from mice with active colitis (17), and in colonic biopsies from IBD patients (21). We now provide direct evidence that IEC-specific CD98 overexpression aggravates intestinal inflammation in a mouse model of DSS-induced colitis, accompanied by massively increased production of proinflammatory cytokines and chemokines.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…overexpression promoted colonic tumorigenesis in mouse models of CAC by aggravating intestinal inflammation, with increased IEC proliferation and induction of proinflammatory cytokines and chemokines crucially contributing to tumor progression (2). Our previous studies demonstrated upregulation of CD98 expression in cultured IECs stimulated with proinflammatory cytokines (19,21), in colonic tissues from mice with active colitis (17), and in colonic biopsies from IBD patients (21). We now provide direct evidence that IEC-specific CD98 overexpression aggravates intestinal inflammation in a mouse model of DSS-induced colitis, accompanied by massively increased production of proinflammatory cytokines and chemokines.…”
Section: Figurementioning
confidence: 99%
“…15), and various human neoplasms (16). Upregulation of CD98 has also been observed in intestinal inflammation in vitro and in vivo (17)(18)(19)(20)(21). Despite the increasing number of studies on this molecule, the potential pathogenetic role of CD98 in CRC, particularly when associated to chronic inflammation, has yet to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…CD98 is a cell surface receptor found to be overexpressed in colonic tissues of mice with colitis, on the surface of intestinal T cells (CD4 + T cells and CD8 + T cells) and B cells of patients with inflammatory bowel disease (IBD) and in intestinal macrophages (34)(35)(36). As CD98 plays an important role in progression of IBD, it can serve as a potential target for therapy of IBD patients.…”
Section: Targeted Sirna Delivery To Macrophages and Colonic Cells To mentioning
confidence: 99%
“…Utilizing an MBP affinity column, we succeeded in the isolation of the major MBP-ligand glycoproteins from cell lysates, and identified them as CD26/dipeptidylpeptidase IV (DPPIV) (110 kDa) (43) and CD98 heavy chain (CD98hc)/4F2hc (82 kDa) (44). PNGase F and endo β-N-acetylglucosaminidase H digestion of these proteins together with MBP-blot analysis suggested that CD26 contained complex-type N-glycans (MLO) that appear to mediate the MBP binding, whereas the CD98 heavy chain consisted almost exclusively of high-mannose type or hybrid type glycans.…”
Section: Identification Of Cd26 As a Major Mlo Carrier Protein In mentioning
confidence: 99%